2018
DOI: 10.1177/0886260518811421
|View full text |Cite
|
Sign up to set email alerts
|

Releasing the Tide: How Has a Shock to the Acceptability of Gender-Based Sexual Violence Affected Rape Reporting to Police in India?

Abstract: National household data suggest that more than four million women in India have experienced nonspousal rape. Fewer than 1.5% of victims of sexual violence in India report their assaults to police, though there is some indication of increased rape reporting to police following a very high-profile fatal gang rape in Delhi in December 2012. This study examines effects of the Delhi gang rape on rape reporting to police in India, and assesses the roles played by geography, media access, and women’s status and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Over time and across contexts, research has shown that considerable barriers exist to reporting rape to the police and that victims receive very little support in reporting from both institutions and discourse (Anderson & Doherty, 2008;McDougal et al, 2018;McMullen, 1990). How reports of rape to the police are met is not static but is contingent on time and place, on contextual factors, and on characteristics of the accuser and the accused.…”
Section: Introductionmentioning
confidence: 99%
“…Over time and across contexts, research has shown that considerable barriers exist to reporting rape to the police and that victims receive very little support in reporting from both institutions and discourse (Anderson & Doherty, 2008;McDougal et al, 2018;McMullen, 1990). How reports of rape to the police are met is not static but is contingent on time and place, on contextual factors, and on characteristics of the accuser and the accused.…”
Section: Introductionmentioning
confidence: 99%
“…Geographical proximity to the focal district could be another pathway of exposure to the shock: regions that are closer to the place of the crime may identify more with the incident and its circumstances, feel more connected to the victim and participate more in street protests and public debates. Findings from McDougal et al (2018) validate this notion; it finds a strong positive association between increase in reported rape and proximity to Delhi. 40 Thus, in the M3 model I check whether the estimated effectstemming from variation in socio-economic exposure to the shock -persists on controlling for physical proximity to the focal district.…”
Section: Empirical Strategymentioning
confidence: 58%
“…Particularly in the Indian context, a few descriptive studies have explored how the 2012rape incident influenced the overall discourse on gender-based violence (Phillips et al, 2015;Nigam, 2012;Lapsia, 2015;Shah, 2019). Further, two recent studies are especially relevant to this paper: McDougal et al (2018), which provides descriptive evidence on increase in reporting of rapes after the incident, using a set of spatial mapping techniques and graphical trend analyses, 14 and Bhatnagar et al (2019), which finds an increase in reported crimes against women after the incident, using a synthetic controls approach. 15 While both these studies yield results consistent with my findings, there are a few important differences in the empirical approach and evidence on mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Most sexual violence in India occurs in marriage; we know less about NMSV due to relatively low reporting ( World Health Organization, 2013 ; Raj & McDougal, 2014 ). Prior research, not specific to India, has found greater risk for sexual violence among women living with economic deprivation ( World Health Organization, 2013 ) and poorer development contexts ( McDougal et al, 2018 ). We believe this study contributes to the research by shedding light on ways to reduce NMSV and is important to the goal of safety for women and girls in India ( Ellsberg et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study involves cross-sectional analyses, and thus we cannot assume causality. Furthermore, we rely on self-reported outcomes of NMSV, which may be underreported ( McDougal et al, 2018 ; Palermo et al, 2014 ). While this analysis is limited to India, further analysis across countries on the relationship between household sanitation and NMSV could increase the generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%